2020
DOI: 10.21203/rs.3.rs-100155/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Involvement of Cervical Muscle Lesions and Autonomic Nervous System in Myalgic Encephalomyelitis / Chronic Fatigue Syndrome (ME/CFS)

Abstract: Background: Patients with myalgic encephalomyelitis / chronic fatigue syndrome (ME/CFS) sometimes coincide with stiffness of cervical muscles. This study examined the effect of local modulation of the cervical muscles on ME/CFS and the underlying mechanism.Methods: In total, 1,226 inpatients with ME/CFS who were resistant to outpatient care were enrolled in this study for 11 years. All patients underwent daily physical therapies to the cervical muscles during hospitalization. Self-rated records documenting the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…The present finding of active HHV-6 infection in the cervical nerve root may propose a potential pathophysiological mechanism for a series of findings by Matsui et al, In 2012, Matsui et al proposed a novel syndrome called "cervical neuromuscular syndrome", which established a link between treating cervical muscle lesions and the alleviation of autonomic dysfunction in ME/CFS (Matsui et al, 2012), which was followed in 2020 with a study establishing a relationship between cervical muscle lesions and parasympathetic nervous system dysfunction (Matsui et al, 2020). These findings were elucidated in a 2021 study in which Matsui et al observed a relationship between treatment of cervical muscle lesions with low frequency electrical stimulation, reduction in severity across a range of ME/CFS symptoms, and reduction of pupil diameter in patients whose symptoms improved (Matsui et al, 2021). Taken together, these findings indicate a relationship between cervical muscle lesions, severity of ME/CFS symptoms, and autonomic dysfunction in ME/CFS, which provide intriguing context for the present identification of active HHV-6 infection in the cervical nerve roots of ME/CFS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The present finding of active HHV-6 infection in the cervical nerve root may propose a potential pathophysiological mechanism for a series of findings by Matsui et al, In 2012, Matsui et al proposed a novel syndrome called "cervical neuromuscular syndrome", which established a link between treating cervical muscle lesions and the alleviation of autonomic dysfunction in ME/CFS (Matsui et al, 2012), which was followed in 2020 with a study establishing a relationship between cervical muscle lesions and parasympathetic nervous system dysfunction (Matsui et al, 2020). These findings were elucidated in a 2021 study in which Matsui et al observed a relationship between treatment of cervical muscle lesions with low frequency electrical stimulation, reduction in severity across a range of ME/CFS symptoms, and reduction of pupil diameter in patients whose symptoms improved (Matsui et al, 2021). Taken together, these findings indicate a relationship between cervical muscle lesions, severity of ME/CFS symptoms, and autonomic dysfunction in ME/CFS, which provide intriguing context for the present identification of active HHV-6 infection in the cervical nerve roots of ME/CFS patients.…”
Section: Discussionmentioning
confidence: 99%